Characterization of Bispecific T-cell Engager (BiTE®) Antibodies with a High-Capacity T-cell Dependent Cellular Cytotoxicity (TDCC) Assay. (April 2015) - Nazarian, Aaron A.; Archibeque, Ivonne L.; Nguyen, Yen H.; Wang, Paul; Sinclair, Angus M.; Powers, David A.
The Bispecific T-cell Engager (BiTE®) antibody modality is a clinically validated immunotherapeutic approach for targeting tumors. Using T-cell dependent cellular cytotoxicity (TDCC) assays, we measure the percentage of specific cytotoxicity induced when a BiTE molecule engages T-cells, redirects T-cell mediated cytolysis, and ultimately kills target cells. We establish a novel luminescence-based TDCC assay quantified by measuring cell viability via constitutive expression of luciferase. The luciferase-based TDCC assay performance is valid and comparable to an adenosine triphosphate (ATP)-based detection method. We demonstrate that the luciferase-based TDCC assay is an efficient homogeneous assay format that is amenable to both suspension and adherent target cells. The luciferase-based TDCC assay eliminates the need for plate-washing protocols, allowing for higher-throughput screening of BiTE antibodies and better data quality. Assay capacity is also improved by performing serial dilutions of BiTE antibodies in 384-well format with an automated liquid handler. We describe here a robust, homogeneous TDCC assay platform with capacity for in vitro assessment of BiTE antibody potency and efficacy using multiple tumor cell lines and T-cell donors.